2014
DOI: 10.14506/ca29.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Managing Hate: Political Delinquency and Affective Governance in Germany

Abstract: The governance of young right-extremists in Germany has spawned a proliferation of therapeutic procedures for their political rectification. This article examines three such efforts in order to expose the excesses and paradoxes that dovetail with, and at times seem to overwhelm, the presumed biopolitical rationality of governance. The penal regimes that bear on young right-extremists call into being a peculiar figure: the political delinquent. In turn, these regimes form part of what I call the management of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…their cultural difference rather than integrate (Holmes 2000;Shoshan 2016:32;Banks and Gingrich 2006). While the German government has adopted numerous approaches to mitigating right-wing extremism in the public sphere (Shoshan 2014;2016), antifascists want a more drastic response to its manifestations: banishment.…”
Section: Fandom As Political Actionmentioning
confidence: 99%
“…their cultural difference rather than integrate (Holmes 2000;Shoshan 2016:32;Banks and Gingrich 2006). While the German government has adopted numerous approaches to mitigating right-wing extremism in the public sphere (Shoshan 2014;2016), antifascists want a more drastic response to its manifestations: banishment.…”
Section: Fandom As Political Actionmentioning
confidence: 99%
“…While historical and ethnographic studies have demonstrated that affective regimes of national belonging are often central to the functioning of citizenship, these studies are equally clear that such linkages are the outcomes of determined projects by states (Kalm 2019; Shoshan 2014; Stoler 2007). In Perón's “New Argentina,” this entailed reimagining the rights attached to citizenship, an outreach to previously marginalized Argentines, and declarations of national and economic sovereignty demonstrated through the nationalization of industries.…”
Section: Affective Citizenshipmentioning
confidence: 99%
“…Despite growing awareness of the role of the middle classes in the global resurgence of conservative movements (Geva 2019; Höjdestrand 2020; Pasieka 2022), scholarly discussion of militarized masculinity and right‐wing activism has disproportionately focused on the gendered performances of disenfranchised working‐class men (Kimmel & Ferber 2000; Miller‐Idriss 2017; Shoshan 2014). One of the reasons for this trend is likely the difficulty of demarcating the boundaries of ‘the middle class’ – an often‐invoked but notoriously slippery category that tends to evade rigorous definition.…”
mentioning
confidence: 99%